Factors Influencing the Uptake of Harm Reduction Services By People Who Inject Drugs in Nairobi, Kenya - Wanyonyi, Joyce Nandako (JOOUST, 2023)
The use of injected drugs leads to significant health and social problems, and harm reduction is the mainstay of managing the effects of the resultant addiction. Currently, there exist two models for the delivery of harm reduction services to the people who inject drugs (PWIDs):drop-in-center (DIC) from where the drug users pick their commodities, and, outreach, in which peer educators collect and deliver commodities to drug users at home or designated areas. This study investigated the uptake of harm reduction services among PWIDs in Nairobi. A mixed methods approach was used to collect primary quantitative and qualitative data from 231 injecting drug users. Questionnaires and key informant interviews were used for 8 peer educators and 4 service providers, respectively. Quantitative data was summarized using descriptive statistics, then inferential statistics derived using SPSS (v. 23) to determine the association between variables (a=0.05). Qualitative data was subjected to thematic analysis. Of the 231 participants, 189 (81.82%) were male, and 158 (68.40%) were aged = 25years. Up to 109 (47.19%) respondents had been using drugs for a period of 4-10 years, and only 26 (11.26%) spent less than KSh. 200/ on drugs each day. Only 94 (40.69%) of the participants had used harm reduction services (HRS) for more than 3 years. Respondents who had used HRS for less than 1 year 2.43 times more likely to utilize HRS than those who had used them for more than 3 years (p<0.05). Knowledge on the organizations that offer HRS (OR= 2.19; p = 0.042), mode of transport to reach the centre (OR=2.04; p = 0.002), always attending each scheduled visit to the centre (OR=1.24, 95% CI 0.28-1.98; p = 0.015), changing the centre for HRS (OR=1.13; p = 0.004), and quality of services from the centre (OR=2.86; p = 0.002) were the individual factors significantly likely to influence HRS utilization. Clients accessing HRS at both DICs and outreaches were 1.34 (p = 0.012) times more likely to utilize HRS than those who only accessed HRS from centres only. In addition, the time taken to get served at a DIC (OR= 3.19; p = 0.001), and quality of services from the DIC (OR=1.43; p = 0.031) were the program related factors significantly most likely to result in HRS utilization. Uptake of HRS was low with poor adherence, although most patients did not change their treatment center, and were generally satisfied with the services offered. Individuals who had used drugs for a shorter duration exhibited higher tendencies to adhere to treatment. Distance to the nearest harm reduction facility, cost of transport, time spent at the facility, and the overall quality of service influenced service uptake. The Ministry of Health, in partnership with various stakeholders, should device mechanisms of identifying persons newly introduced to injection drugs, and promptly initiate harm reduction. It should also map out those who inject drugs, and eradicate outlets for illicit drugs. In addition, it should improve access and quality of service by initiating more treatment centers, and employing more providers with adequate skills.
Keywords: Injected drugs